The Effect of Warm Water Compress and Back Massage On Labor Pain At Active Phase At Kartini Hospital In 2020 - Suralaga, Cholisah; Dwi, Andika; Dinengsih, Sri (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This research was carried out through a quasi-experimental study involing two groups, in which pre-test and post-test design were used. Results revealed that the mean value of labor pain during the first stage of active phase before warm water compresses was given was 8.40 with a standard deviation of 0.632 and after giving warm water compress, the mean value of labor pain was 4.40 with a standard deviation of 2.131. Whereas, in the back massage, the mean labor pain scale before back massage was given was 8.33 with a standard deviation of 0.979 and after giving back massage the average labor pain became 3.73 with a standard deviation of 1.981. It can be summed up that there was an effect of giving warm water compress and back massage on labor pain during the active phase, but neither method was superior in reducing labor pain seen from p value 0.382> 0.05.